Tanggung Jawab Bank Terhadap Nasabah Atas Berkurangnya Dana Akibat Skimming Dalam Rekening Bank - Kadek Ayu Manik Gita Shintadewi; I Nyoman Putu Budiartha; I Made Minggu Widyantara (Jurnal Analogi Hukum, 2021)
The progress of the banking system cannot be separated from the role of information technology. A crime related to banking that is currently being discussed is Skimming Skimming, which was carried out by stealing customer data stored in a magnetic strip on an ATM card and transmitted wirelessly.and 2 problem formulations,namely 1.How the bank's responsibility to customers for reduced funds due to skimming in bank accounts?2.What the process carried out by banks and customers for reduced funds due to skimming in bank accounts?type of research is normative legal research, the approach method is legislation, legal material collection techniques are to study, study and process legal material. The results of the study state that the bank as a business actor in the form of a legal entity is responsible for providing compensation for losses from consumers, namely customers due to service products provided, namely e-banking services through electronic media,efforts made by banks and customers for reduced funds due to skimming. the bank can tighten the security when transactions are carried out, especially at ATMs, for customers if they experience a skimming incident, they should immediately report it to the bank.